(untitled) (Medico Legal Update, 2020)
Introduction and Objectives: Snake bite is one ofthe public health problem often neglected, especially in tropical and developing countries of the world. Demographic and clinical parameters changes in different parts of the world. In India it is more prevalent in Kerala, Karnataka, Maharashtra, Tamilnadu, etc. This study was conducted in a tertiary health care centre in Maharashtra to demonstrate the epidemiology, management and severity of snake bite as an acute medical emergency situation to create awareness regarding the first aid treatment and to formulate policies for ASV availability. Materials and Method: Tertiary health care based retrospective study was conducted from June 2017 to July 2018 and data was collected, analyzed and presented as percentage. Results: In this present retrospective study a total of 131 cases of snake bites were observed in a tertiary health care centre and the mortality rate was found to be 1.53%. More than 50% bites were of Vasculotxic Snake leading to severe systemic complications in 15% of the victims and death of 2 patients, ASV was required in 68% cases of snake bites. Conclusion: To lower the incidences of Snake bites, awareness and preventive measures such as avoiding tall grassy areas, keeping storage areas clear of rodents, removing rubbish, raise beds above floor level and avoiding areas known to harbor dangerous snakes. Use of gumboots and long pants for working outdoors is advised. First aid treatment and assurance to patients are the most important primary management of Snake bites.